Kształtowanie partnerstwa przedsiębiorstwa z klientami w warunkach globalizacji - Piwoni-Krzeszowska, Estera (Shaping corporate partnership with clients in globalisation, 2005)
Nowadays, all enterprises need to think globally even if they operate locally. Shaping partnership with clients is particularly important for enterprises that operate in the market of a given country or a region of the world. It is one possible way for an enterprise to make itself distinct from the global competition. For enterprises that are geocentrically-oriented in their approach to creating customer relationships, the safety-pin strategy seems to be more appropriate. In turn, for enterprises that are ethnocentrically-oriented, policentrically-oriented or regiocentrically oriented in their approach to creating customer relationships, the zipper strategy can also be applied.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 183-190